Legal Power in the Mother Surrogate Agreement in the Notary Deed - Habib Adjie; Muhammad Nur Hamzani (Budapest International Research and Critics University, 2022)
Implementation of uterine rental agreement or surrogate mother is an agreement between a woman who binds herself through an agreement with another party (husband and wife) to become pregnant with the result of the fertilization of the husband and wife which is implanted into her womb, and after giving birth is required to hand over the baby to the husband and wife based on agreement made. The research method used is normative legal research, namely legal research conducted by researching library materials or secondary legal materials, while the problem approach is carried out using a legal approach and a conceptual approach. The results of the study indicate that the mother surrogate does not fulfill one of the conditions of the agreement. Then the Notary Deed is declared null and void if the deed does not meet the objective elements of the deed, namely a lawful cause. In such a case, legally without any request from the parties, thus the agreement is considered to have never existed and is not binding on anyone.